Surgical Treatment of Sacral Metastatic Tumors - Sun, Mengxiong; Zuo, Dongqing; Wang, Hongsheng; Sheng, Jiakang; Ma, Xiaojun; Wang, Chongren; Zan, Pengfei; Hua, Yingqi; Sun, Wei; Cai, Zhengdong (Frontiers in Oncology, 2021)
Objective This study intends to retrospectively analyze the data of patients with sacral metastases in our center, and analyze the treatment methods and therapeutic effects of sacral metastases. Methods 73 patients with sacral metastases treated in our hospital from June 2013 to June 2019 were retrospectively analyzed. There were 54 cases of neurological symptoms, 42 cases of sacroiliac joint instability, 24 cases of lower limb muscle weakness and 19 cases of abnormal urination and defecation. Four patients with tumors below S3 underwent complete tumor resection, 23 patients with tumors above S3 and without sacroiliac joint instability underwent tumor curettage and nerve root lysis, 34 patients with tumors above S3 and sacroiliac joint instability underwent tumor curettage, nerve root release and screw rod reconstruction. 12 patients with multiple metastases underwent percutaneous radiofrequency ablation and sacroplasty. VAS was used to evaluate the preoperative and postoperative pain scores, and the postoperative pain relief, neurological function, bowel function, wound healing and complications were evaluated. Results There were no perioperative death, 8 cases of poor wound healing, 5 cases of nerve injury, postoperative sensory and motor loss of lower limbs. Cerebrospinal fluid (CSF) leak in 7 cases. The patients were followed up for 6-25 months (mean 12 months). The VAS scores of patients with pain symptoms were 7 points before operation and 1.44 points after operation, In 19 patients with abnormal urination and defecation function, 12 patients recovered to normal 3-6 months after operation, 5 cases had no significant change compared with preoperative, and 2 cases had aggravated symptoms; 17 cases of patients with lower limb muscle strength were significantly recovered after operation, and the average muscle strength was increased by 2 grades; 30 cases of patients with unstable sacroiliac joint got internal fixation had significantly pain relief. Pain symptoms of 9 patients were significantly relieved after percutaneous radiofrequency ablation. Conclusion the operation of sacral metastases mainly adopts a relatively conservative surgical method, which can effectively improve the quality of life of patients with sacral metastases by retaining the nerve function and relieving the pain of patients, combining with radiofrequency ablation, sacroplasty and targeted drugs.